A Future for the Inland Fish and Fisheries Hidden Within the Sustainable Development Goals - Vittoria L. Elliott; Vittoria L. Elliott; Abigail J. Lynch; Sui C. Phang; Steven J. Cooke; Ian G. Cowx; Julie E. Claussen; James Dalton; William Darwall; Ian Harrison; Karen J. Murchie; E. Ashley Steel; et al. (Frontiers in Environmental Science, 2022)
The United Nations Sustainable Development Goals (SDGs) are a unifying call for change - guiding global actions at multiple levels of governance for a better planet and better lives. Consequently, achieving the “future we want” may be hindered by overlooking valuable natural resources and services that are not explicitly included in the SDGs. Not recognizing the direct, intrinsic value of some natural resources may threaten the sustainability of the services they provide and their contributions to the SDGs. Here, we use inland aquatic ecosystems, and the fish and fisheries therein, as an example to explore opportunities for recognition and inclusion of other natural resources that are missing from the SDGs. Key resources absent from the SDGs are less likely to be incorporated in global, national, and regional objectives, dialogues, and policies. We outline multiple potential pathways for better inclusion and capitalization of contributions from these overlooked natural resources during the operationalization of the SDGs and other global instruments.